PENGARUH MEDIA PEMBELAJARAN BERBASIS VIDEO TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DI SMP NEGERI 2 SIMANINDO - Meiliastry Simarmata, Enjellita; Nurliani Siregar; Imelda Butarbutar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This thesis was supervised by Rev. Dr. Nurliani Siregar, S.Ag., M.Pd and Rev. Imelda Butarbutar, S.Th., M.Psi., M.Pd at the Faculty of Teacher Training and Education (FKIP), HKBP Nommensen University, Medan. This study aims to determine the effect of the use of video learning media on student achievement in Christian Religious Education in seventh-grade students at SMP Negeri 2 Simanindo. This research was quantitative, using a quasi-experimental design using a two-group pretest-posttest design. The sample size was 55 students, divided into two groups: an experimental class (using video media) and a control class (using conventional methods). Data were collected through a multiple-choice test (20 items) that had been tested for validity and reliability, a questionnaire (60 items), and a student activity observation sheet. The pretest results showed no significant difference between the initial abilities of the experimental class (average 49.0) and the control class (average 45.61), with a calculated t value (1.3099) < t table (2.0032). After treatment, the average posttest score of the experimental class increased significantly to 80.39, while the control class only achieved 65.96. A one-tailed hypothesis test yielded a calculated t value (5.905) > t table (2.0032), indicating that Ha was accepted. This demonstrates the positive and significant influence of the use of video-based learning media on student achievement in Christian Religious Education (PAK). The regression equation Y = 76.09 + 0.035 X indicates a positive relationship between the use of video media and improved learning outcomes.